Capturing city-transport interactions. An analysis on the urban rail network of Palermo (Italy) - Elif Sezer; João Igreja; Ignazio Vinci (TeMA: Journal of Land Use, Mobility and Environment)
Transit Oriented Development (TOD) and 15-minute City (15mC) are two planning concepts that, in different ways, have attempted to provide alternative solutions to the car-centered development model characterizing modern cities. The paper presents a methodology that seeks to integrate the TOD and 15mC principles in an analytical perspective, with an application in a rail station area of Palermo, a Southern European city plagued by inefficient public transport and traffic congestion. The study aims to define and compare two different station areas based on their socio economic, functional and environmental dimensions including accessibility and built environment. The paper is divided into six sections, including the work’s theoretical framework, the description of the railway system, the methodology that explains indicators used for the analysis and discussion about the comparison of two case studies. In the final part of the paper we critically outline the potential of this approach for future investigations and explain the novelty of the research with integrated analysis of the city-transport interaction around two different node.